SISTEM KOMUNIKASI PEMERINTAH DAN KOMPLEKSITAS PENGETAHUAN PETUGAS PENYULUH LAPANGAN - Tatag Handaka; Hermin Indah Wahyuni; Endang Sulastri; Paulus Wiryono (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
Purworejo district government has given extension techniques of Kaligesing goat breeding through Field Extension Officer (PPL) to the breeders.However, breeders assess the knowledge and experience of Field Extension Officer (PPL) has not been optimal in the breeding of Kaligesing goat. The aim of this research is to know how the government’s communication system adapts to the complexity of Field Extension Officer (PPL)knowledge that has not been optimal in the breeding of Kaligesing goat. The theory of the research is communication system in perspective of Niklas Luhmann. The research was used explorative case study method.Population of the research in Purworejo regency which was the center of Kaligesing goat farming.The result of the study shown that the government’s communication system in facing the complexity of Field Extension Officer (PPL) knowledge that has not been optimal, has produced and reproduced the form of training, comparative study, and provision of pilot land. But government communication system not effective in reducted and selected feedback from Field Extension Officer (PPL). So reproduction of regulation not solved environment complexity. Production and reproduction of regulation from government communication system not adaptive with environment complexity.